Mildly Increased Renin Expression in the Absence of Kidney Injury in the Murine Transverse Aortic Constriction Model - Marian Wesseling; Marian Wesseling; Eva Mulder; Maike A. D. Brans; Daniek. M. C. Kapteijn; Marian Bulthuis; Gerard Pasterkamp; Marianne C. Verhaar; A. H. Jan Danser; Harry van Goor; Jaap A. Joles; Saskia C. A. de Jager; et al. (Frontiers Media S.A., 2021)
Cardiorenal syndrome type 2 is characterized by kidney failure as a consequence of heart failure that affects >50% of heart failure patients. Murine transverse aortic constriction (TAC) is a heart failure model, where pressure overload is induced on the heart without any systemic hypertension or its consequences. Whether renal function is altered in this model is debated, and if so, at which time post-TAC renal dysfunction starts to contribute to worsening of cardiac function. We therefore studied the effects of progressive heart failure development on kidney function in the absence of chronically elevated systemic blood pressure and renal perfusion pressure. C57BL/6J mice (N = 129) were exposed to TAC using a minimally invasive technique and followed from 3 to 70 days post-TAC. Cardiac function was determined with 3D ultrasound and showed a gradual decrease in stroke volume over time. Renal renin expression and plasma renin concentration increased with progressive heart failure, suggesting hypoperfusion of the kidney. In addition, plasma urea concentration, a surrogate marker for renal dysfunction, was increased post-TAC. However, no structural abnormalities in the kidney, nor albuminuria were present at any time-point post-TAC. Progressive heart failure is associated with increased renin expression, but only mildly affected renal function without inducing structural injury. In combination, these data suggest that heart failure alone does not contribute to kidney dysfunction in mice.